Simulations of spectra and some physical attributes of specific homologous series of nematic liquid crystals in the range of 0.4–7.6 THz - Sielezin, Karol; Kowerdziej, Rafał; Chodorow, Urszula; Olifierczuk, Marek; Parka, Janusz (Photonics Letters of Poland, 2025)
In this research, we provide the outcomes of spectral calculations and selected characteristics of the NLC homologous series of cyanobiphenyls (nCB) and phenylcyclohexanes (nPCH) within the frequency range of 0.4–7.6 THz. Geometry optimizations, assessments of harmonic frequencies, and calculations of intensity were performed utilizing Scigress – Molecular Modelling Software developed by Fujitsu. The numerical analyses were executed following the standard DFT procedure, employing the B88-LYP functional and DZVP basis sets. The results obtained for the absorption spectra, along with physical parameters such as dielectric permittivity, refractive index, and birefringence, are detailed herein. Notably, we demonstrate that the results align well with the referenced experimental findings. Full Text: PDF References J. Parka, K. Sielezin, "0.3-10.0 THz spectra for chosen liquid crystal molecules - simulation and physical properties", Mol. Cryst. Liq. Cryst., 657, 66 (2017). CrossRef K. Sielezin, R. Kowerdziej, J. Parka, "Simulations of some physical parameters of homologous series of nBT and nCHBT at 0.3-20.0 THz", Liq. Cryst., 1563918, 1 (2018). CrossRef Z. Chen, L. Jiang, H. Ma, "Calculation on frequency and temperature properties of birefringence of nematic liquid crystal 5CB in terahertz band", Chem. Phys. Lett., 645, 205 (2016). CrossRef Z. Chen, Y. Jiang, L. Jiang, H. Ma, "Terahertz absorption spectra and potential energy distribution of liquid crystals", Spectrochim. Acta A Mol. Biomol. Spectrosc. 153, 741 (2016). CrossRef Z. Chen, Y. Jiang, L. Jiang, H. Ma, "Molecular vibration mode assignment of nematic liquid crystal 5CB on Terahertz spectra", Liq. Cryst., 42(7), 947 (2015). CrossRef N. Vieweg, M. A. Celik, S. Zakel, V. Gupta, G. Frenking, M. Koch, "Terahertz Absorption of Nematic Liquid Crystals", J. Infrared Milli Terahertz Waves 35, 478 (2014). CrossRef P. Friebel, D. R. Galimberti, M. Savoini, L. Cattaneo, "Unveiling Low THz Dynamics of Liquid Crystals: Identification of Intermolecular Interaction among Intramolecular Modes", J. Phys. Chem. B 128, 596 (2024). CrossRef Molecular Modelling Software SCIGRESS, Fujitsu Limited, Tokyo, Japan, (2016), DirectLink R. Kowerdziej, L. Jaroszewicz, M. Olifierczuk, J. Parka, "Experimental study on terahertz metamaterial embedded in nematic liquid crystal", Appl. Phys. Lett., 106(9), 092905 (2015). CrossRef M. Olifierczuk, R. Kowerdziej, L. Jaroszewicz, M. Czerwinski, J. Parka, "Numerical analysis of THz metamaterial with high birefringence liquid crystal", Liquid Crystals, 39(6), 739 (2012). CrossRef R. Kowerdziej, T. Stańczyk, J. Parka, "Electromagnetic simulations of tunable terahertz metamaterial infiltrated with highly birefringent nematic liquid crystal", Liquid Crystals, 42(4), 430 (2015). CrossRef J. Parka, S. Kłosowicz, "16th Topical Meeting on the Optics of Liquid Crystals", Phot. Lett. Poland, 7(4), 90 (2015). CrossRef U. Chodorow, J. Parka, O. Chojnowska, "Liquid Crystal Materials in THz Technologies", Phot. Lett. Poland, 4(3), 112 (2015). CrossRef